Lygaeoidea (Insecta: Hemiptera): taxonomy, diversity and distribution in Brazil, with a review of the tribe Lethaeini in the Neotropics - Carrenho, Renan (2023)
The most diverse family of the Lygaeoidea (Hemiptera: Heteroptera) is Rhyparochromidae,especially for the Neotropical region. Most rhryparochromids species inhabit groundlitter,and exhibit seed predation behavior, eequiring specialized sampling techniques. Becauseoftheir minute size, they are relatively neglected. This work is focused on the studyof thediversity of the Lygaeoidea from Brazil, with emphasis in the tribe Lethaeini of theAmericas.We show that Lethaeus lepidus is a junior synonym of Petissius spinipes withsignificantimplications for the representation of Lethaeus in the New World. Followed by diagnosis,keys for genera and species, and new records distributional maps for the tribeintheAmericas. In a broader context, a phylogeny for the Lethaeini with morphological dataisinferred in order to test the monophyly of the New World generic group includingall lethaeini genera with one iridescent are on the base of the head, and the relationshipbetween them. Additionally, we discuss the the classification and the relationshipof theall Lethaeini genera currently known in the New World. As a result, Lethaeini is foundtobenon-monophyletic in the analyses. This is observed because one representative of thetribeAntillocorini was nested within American genera. Additionally, American Lethaeini generadid not form a monophyletic group, nor did the group of genera with one iridescent areaonthe base of the head. The relationships between genera showed changes under analyses.However, the monophyly of the genera some genera was consistently supportedinthe analyses.